An adaptive real‐time energy management system for a renewable energy‐based microgrid. Issue 13 (31st May 2021) - Zeinal‐Kheiri, Sevda; Mohammadpour Shotorbani, Amin; Khardenavis, Amaiya; Mohammadi‐Ivatloo, Behnam; Sadiq, Rehan; Hewage, Kasun
Abstract: This paper proposes an adaptive real‐time energy scheduling method (RT‐EMS) for a microgrid, using a Lyapunov optimization ‐based real‐time approach. Inaccuracy in day‐ahead predictions can result in non‐optimal solutions to the energy scheduling problem. Although the real‐time optimization method eliminates the need to deal with the prediction uncertainties, it ignores the valuable statistical information used in day‐ahead stochastic approaches and provides suboptimal solutions to the problem. The proposed adaptive approach combines the advantages of both the stochastic day‐ahead and the RT‐EMS and reduces the real‐time operational cost of the microgrid. The proposed method moves the RT‐EMS solution towards the optimal solution, by adding a penalty term to the objective function. Numerical results are provided to demonstrate the improved performance of the proposed adaptive method.